An Analysis on Students’ Ability in TOEFL Structure Section Tests of Sixth Semester at Batanghari University Academic Year 2016/2017 - Asma Ariska; Wennyta Wennyta; Nurul Fitri (JELT: Journal of English Language Teaching, 2017)
AbstractThe aim of this research is to know the students’ ability in TOEFL Structure Section tests of sixth semester at Batanghari University Academic Year 2016/2017. The sample of this research are 20 students sixth semester at Batanghari University which consist of two classes, regular A and B. The design of this research is descriptive method because the researcher just analysis the students’ ability in TOEFL Structure Section test. Based on the data analysis, the sixth semester students of English Education Study Program attained 60% which belong to fair category in Structure and Written Expression part. Based on the result of the research and the discussions that have been previously discussed in chapter IV, it can be concluded that the students’ ability in TOEFL Structure Section tests of sixth semester of English Education Study Program at Batanghari University was 60%, it belong to fair category. Keywords: Students’ Ability, TOEFL Structure Section Tests